2014
DOI: 10.1002/etc.2533
|View full text |Cite
|
Sign up to set email alerts
|

The naturally occurring carcinogen ptaquiloside is present in groundwater below bracken vegetation

Abstract: The present study demonstrates unequivocally the presence of the natural carcinogen ptaquiloside and its transformation product pterosin B in groundwater and surface water. Groundwater concentrations up to 0.23 nmol/L (92 ng/L) ptaquiloside and up to 2.2 nmol/L (0.47 µg/L) pterosin B were found. Of 21 groundwater samples, 5 contained ptaquiloside, exceeding the estimated threshold for drinking water (1.3-40 pmol/L). The results are critical for water abstraction in bracken-infested areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
(45 reference statements)
2
31
0
Order By: Relevance
“…Ptaquiloside presence was recently confirmed in Danish groundwater and surface water and the risk of human exposure through consumption of shallow, untreated groundwater was highlighted [19]. In our study, ptaquiloside was observed at all three drinking water abstraction sites in October 2015.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Ptaquiloside presence was recently confirmed in Danish groundwater and surface water and the risk of human exposure through consumption of shallow, untreated groundwater was highlighted [19]. In our study, ptaquiloside was observed at all three drinking water abstraction sites in October 2015.…”
Section: Discussionsupporting
confidence: 71%
“…Research underpinning quantification of ptaquiloside, and associated risk to humans and animals has expanded in the past decade, with most recent studies reporting on the fate of ptaquiloside in receiving water [19,33], animal plasma, urine and milk [34]. The proximity of bracken to drinking water supply sources and the absence of any relevant data on ptaquiloside in Ireland prompted the current investigation which has provided further evidence on the distribution of ptaquiloside in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also used in foods and medicine, mainly in Asia, and is a known contaminant in milk produced by cows, sheep, and goats browsing on bracken [38]. There is ample evidence to show its presence in surface [39] and groundwater [40], and thus ptaquiloside may eventually contaminate drinking water (Figure 1). Although the suspected carcinogenicity of ptaquiloside has been known for a long time and there are epidemiological studies that suggest it to cause esophageal and stomach cancer in humans [41,42], there is little or no monitoring, regulation, and control of ptaquiloside in strong contrast to the regulation of, e.g., pesticides in drinking water, even though they may not be as toxic as ptaquiloside.…”
Section: Ptaquilosidementioning
confidence: 99%